Adolescents’ Perceptions of Career Concern: Student Discouragement in Career Development - Code, Michael N.; Bernes, Kerry B.; Gunn, Thelma M.; Bardick, Angela D. (Canadian Journal of Counselling and Psychotherapy, 2007)
This study used the Comprehensive Career Needs Survey to assess how junior high and high school students perceive career concerns and how these concerns may change from Grades 7 to 12. An examination of participants’ responses about the sources of their discouragement in career planning revealed seven themes: training and education concerns, security, satisfaction, failing, commitment, wrong occupational choice, and having to decide. Implications for career professionals are discussed.